Phenomenological Psychology as Announced by Edmund Husserl. (Phenomenology, Humanities and Sciences, 2023)
Between 1925 and 1928, Edmund Husserl produced a series of reflections on the which should be a phenomenological psychology and its relationship with transcendent phenomenology, present in Husserlian IX, with the title of “Phenomenological Psychology” (Phänomenologische Psychologie). These writings are constituent parts of the summer semester lectures 1925, added to the fourth and final version of the article destined for the Encyclopedia Britannica, the Amsterdam Conferences and, additionally, some very illustrative appendices of what it had been broadly conceived as phenomenological psychology.
Keywords: Edmund Husserl